Peran Guru Bimbingan Konseling dalam Meningkatkan Konsep Diri Siswa di Masa Pandemi Covid-19 - Beni Azwar; Miftakhul Jihan Cahyati (Institut Agama Islam Negeri Curup, 2023)
This study aims to determine the role of guidance and counseling teachers in improving students' self-concept during the covid 19 pandemic. It can be seen that students cannot do assignments, feel depressed because they do not leave the house to socialize with their friends. This type of research is mixed method research with the embedded design with descriptive methods which aims to describe the state of students' self-concept during covid-19 and the role of counseling teachers in improving students' self-concept during covid-19, with 42 respondents, 2 counseling teachers and 1 student's parents. Data collection techniques using observation, questionnaires, interviews and documentation. The data validity technique used is triangulation of sources and techniques. The results showed that the condition of students' self-concept in the covid-19 period was quite good because 45% of students answered always, 32% of students answered often, 16% of students answered rarely and 8% of students answered never. As well as the role of counseling teachers by always monitoring the development of their students through WA groups and inviting students to think positively, recognize (understand and accept) themselves well, help students evaluate themselves and their career planning.